Moderating effect of business environmental dynamism in the innovativeness: Company performance relationship of Congolese manufacturing companies - Remo Metalor Ruba; Germinah E. Chiloane-Tsoka; Thea Van der Westhuizen (Economies, 2023)
Research has shown that innovativeness is a key factor in business performance. However, the link between innovativeness and organisational performance and the role of environmental dynamism are still being debated. This study thus sought to analyse the moderating effect of the dynamism of the business environment in the relationship between innovativeness and performance of manufacturing companies. In order to do this, a questionnaire was distributed to 344 owners and managers of manufacturing companies operating in the north-eastern Democratic Republic of Congo. One hundred and seventy-eight of these questionnaires were returned and used to test the study's hypotheses. The study used an ordinary least squares (OLS) regression under the hierarchical regression analysis approach. The results confirm the positive and significant effect of innovativeness on company performance. On the other hand, results indicate that business environmental dynamism has a direct positive and significant effect on company performance. However, the dynamism of the business environment negatively influences the relationship between innovativeness and company performance. Based on these results, recommendations and further research perspectives are suggested.
Keywords: 330; company performance; north-eastern Democratic Republic of Congo; environmental dynamism; innovativeness; manufacturing companies